PREVALENCE AND CONTRIBUTING FACTORS TO FRAILTY AND FALLS AMONG COMMUNITY-DWELLING OLDER ADULTS IN NORTH-CENTRAL NIGERIA (Journal of Biomedical Investigation, 2023)
Background: Frailty and falls are becoming more important health issues as the population ages. The lack of information and understanding about falls and frailty limits the benefits of general care for the elderly. The study investigated the prevalence and factors contributing to falls and frailty in North[1]Central Nigerian communities.Methods: This was a cross-sectional study of 494 older adults aged 60-110 years, who were mostly Tiv residing in Benue State, Nigeria. The Fried Frailty Phenotype (FFP) scale was used to assess their frailty status, and information regarding falls (two or more times) over the past year was collected. Multivariate logistic regression was performed to determine factors that increased frailty and falls in older adults.Results: A total of 494 older adults with mean age, 76.411.23 years participated in the study. Frailty and falls were reported to be prevalent in 62.9% and 33.2% of participants, respectively. The results of the study further indicated that the prevalence of both frailty and falls was higher in those who were older (≥85 years) and those without formal education. The risk of falling (odds ratio = 0.51; 95%CI: 0.31 to 0.86) and frailty (odds ratio = 0.39; 95%CI: 0.22 to 0.69) were also significantly lower in males as compared to females. Frailty and falls were also more prevalent in smokers and those with poor functional status.Conclusion: Among older rural residents, frailty and falls are common, especially among women, smokers, and those with poor physical health. The aging population may require lifestyle interventions because of frailty and falls.
Keywords: Frailty; falls; older adults; community dwelling; North-Central Nigeria